2022
DOI: 10.1007/s00204-022-03387-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation and detoxification of organophosphorus pesticides in freshwater planarians shares similarities with humans

Abstract: Organophosphorus pesticides (OPs) are a chemically diverse class of insecticides that inhibit acetylcholinesterase (AChE). Many OPs require bioactivation to their active oxon form via cytochrome P450 to effectively inhibit AChE. OP toxicity can be mitigated by detoxification reactions performed by carboxylesterase and paraoxonase. The relative extent of bioactivation to detoxification varies among individuals and between species, leading to differential susceptibility to OP toxicity. Because of these species d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 89 publications
(127 reference statements)
0
9
0
Order By: Relevance
“…The worms are now ready for imaging but can be stored at 4°C in the dark for a few days before mounting and imaging. Specificity of the staining can be determined using concentrations of AChE inhibitors known to inhibit AChE in planarians, such as physostigmine or OPs like diazinon (Hagstrom et al, 2018;Ireland et al, 2022aIreland et al, , 2022b.…”
Section: Stainingmentioning
confidence: 99%
See 2 more Smart Citations
“…The worms are now ready for imaging but can be stored at 4°C in the dark for a few days before mounting and imaging. Specificity of the staining can be determined using concentrations of AChE inhibitors known to inhibit AChE in planarians, such as physostigmine or OPs like diazinon (Hagstrom et al, 2018;Ireland et al, 2022aIreland et al, , 2022b.…”
Section: Stainingmentioning
confidence: 99%
“…Several research groups have shown that AChE activity can be detected in various planarian species (Bullock & Nachmansohn, 1942; De Simone et al., 1994; Villar et al., 1994; Zheng et al., 2011). We have shown that AChE activity can be detected during all stages of neurodevelopment in D. japonica planarians (Ireland et al., 2022a). This species is also sensitive to and can metabolize organophosphorus pesticides (Hagstrom et al., 2017; Ireland et al., 2022a).…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be established what the context of use is for the planarian system, considering its unique strengths and limitations. We need to better understand the toxicokinetics and toxicodynamics of planarians, as only limited studies of planarian xenobiotic metabolism have been undertaken (Ireland, Rabeler, Gong, & Collins, 2022). How does planarian screening complement other models when integrated into a DNT test battery?…”
Section: Current and Future Chall-enges For Planarian Nt/dnt Studiesmentioning
confidence: 99%
“…Organophosphorus compounds play a major role in chiral pesticide pollutants because this type of agrochemicals is the most produced and applied plant protection agent in the world. , Especially in some developing countries such as Brazil, China, and India, the usage of organophosphorus pesticides even reaches more than 60–70% of the total amount of pesticides. , However, commercial organophosphorus pesticides are sold and used in the form of racemate for a long time, without strict discrimination between single enantiomers, which will entail a serious threat to human health. , Zhang et al found that chiral organophosphorus malaoxon, isomalathion, and methamidophos have very similar enantioselectivity to target acetylcholinesterase (AChE) on the inhibition kinetics and postinhibitory reactions of acid α-naphthyl acetate esterase, which will greatly increase the risk of these organophosphates to human health. The results of wet experiments and computational chemistry reported by Zhang et al clearly unknot that ( R )-trichloronate, ( S )-leptophos, and ( R )-fonofos have significantly stronger inhibitory activity and affinity for human AChE than their antipodes, and they further argued that the toxicity risk of racemic organophosphorus pollutants presented widely in the environment needs to be reassessed.…”
Section: Introductionmentioning
confidence: 99%